Analisis Pengaruh Faktor Ekonomi terhadap Utang Luar Negeri di Tujuh Negara ASEAN Tahun 1999-2023 - Barsua, Ni Putu Esti Utami; Ramadhani, Anindita Ayu; Ashari, Bagas; Iqbal, Naufal Muhammad; Yuliana, Rita (Seminar Nasional Official Statistics, 2025)
The debt-to-GDP ratio in seven ASEAN countries indicates moderate to high levels, accompanied by fiscal pressures due to exchange rate fluctuations and dependence on external financing. This condition reflects serious challenges in managing external debt that may affect regional economic stability. This study analyzes the influence of macroeconomic factors on external debt in seven ASEAN countries (Indonesia, Thailand, Philippines, Myanmar, Cambodia, Laos, and Vietnam) over the period 1999–2023. Using panel data regression with the Fixed Effects Model (FEM) and Seemingly Unrelated Regression (SUR) estimation, the results show that GDP per capita and foreign direct investment (FDI) have significant negative effects, while the labor force participation rate (LFPR) and inflation have positive effects. Higher economic welfare and FDI flows reduce debt dependency, while high inflation and labor market imbalance encourage external borrowing. The findings underscore the urgency of prudent macroeconomic policy and sustainable fiscal strategies to ensure long-term regional stability.